Evolution of Low‐Frequency Vibrational Modes in Ultrathin GeSbTe Films. Issue 3 (19th November 2020) - Zallo, Eugenio; Dragoni, Daniele; Zaytseva, Yuliya; Cecchi, Stefano; Borgardt, Nikolai I.; Bernasconi, Marco; Calarco, Raffaella
Abstract : GeSbTe (GST) phase‐change alloys feature layered crystalline structures made of lamellae separated by van der Waals (vdW) gaps. This work sheds light on the dependence of interlamellae interactions at the vdW gap on film thickness of GST alloys as probed by vibrational spectroscopy. Molecular beam epitaxy is used for designing GST layers down to a single lamella. By combining density‐functional theory and Raman spectroscopy, a direct and simple method is demonstrated to identify the thickness of the GST film. The shift of the vibrational modes is studied as a function of the layer size, and the low‐frequency range opens up a new route to probe the number of lamellae for different GST compositions. Comparison between experimental and theoretical Raman spectra highlights the precision growth control obtained by the epitaxial technique. Abstract : The shift of the vibrational modes of Ge2 Sb2 Te5 films obtained by molecular beam epitaxy is studied as a function of the layer size down to a single lamella. The low‐frequency range is related to the interactions between layers in the film and opens up a new route to probe the number of lamellae for different GeSbTe (GST) compositions.